Characteristic of the game of the world top-level woman choppers in table tennis: Focusing on the using technique - Nonaka, Y.; Ando, S.; Yamada, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
This study aimed to clarify the characteristics of the games played by every world top-level women chopper by studying eight players (A-H) using notational game performance analysis. The games sample comprised six games per player, 48 games in total, from the 2013-2015 world championship and International Table Tennis Federation World Tour. Analysis items were the number of shots played per rally, the utilization, the winning and the losing ratios according to the classification of techniques, the utilization ratios of each techniques belonging to the classification. It also considered utilization ratios of various attacking combinations and the techniques used before an attack. The data obtained were processed using statistical methods such as Fisher's exact test and the Kruskal-Wallis test. The main results were as follows: 1) In terms of the average number of shots played per rally, more losing rallies than winning rallies were observed. Furthermore, winning ratios for 1-3 shots of the rally were high, except for H while they were low for 4-9 shots. Winning ratios after 10 shots of the rally were high in three players, who had higher world rankings while they were low in other players. 2) The utilization of an attack was 16% of maximums. In addition, losing ratios for attack for a high-ranking player were less than 25% while they were high for other players. 3) The total percentages for the chop and the push were 81% of maximums and 62% of minimums. Moreover, some players mainly utilized the chop while others mainly utilized the push. 4) The utilization ratios of the various attack different for each player, and these could be classified into five types: Forehand counter loop drive (Fhdr), Backhand smash (Bsm), Forehand speed drive (Fsdr), Forehand smash (Fsm), and Backhand speed drive (Bsdr). 5) The utilization ratios for all players had more backhand chop (Bc) than forehand chop (Fc) and more backhand push (Bt) than forehand push (Ft), except for one player. This was considered to be common for all world-class choppers. 6) The utilization ratios of the technique used before an attack were different for each player, and these techniques could be classified into three types: the chop, the push, and the service before the attack.